Os saguis do gênero Leontopithecus Lesson, 1840 (Callithricidae - Primates) - Coimbra Filho, Adelmar Faria (1976)
The systematic position of the forms of Leontopithecus Lesson,1840, is reviewed, with comments on the taxonomic history and genetic affinities of the representatives of this genus. Morphological aspects are described as well as the first and only known case of hybridization between two forms of the genus. Emphasis is on the behavior of these tamarins, especially the active participation of immature individuals in the rearing of younger siblings. Their rather prolonged stay by the parents ' side is of major importance in the acquisition of normal psychoreproductive development. This fact has great significance for projects aimed at reproducing species of Callithricidae in captivity. The size of groups of individuals varies, usually ranging from two to eight lion tamarins. However, larger groups may be formed temporarily. The three subspecies of Leontopithecus are found only in restricted areas of three states in Southeastern Brazil - L. r. rosalia in Rio de Janeiro, L.r.chrysomelas in Bahia, and L.r.chrysopygus in São Paulo. In the forest, individuals of these subspecies occupy the intermediate strata. Their diet is made up basically of wild fruits, arthropods, small vertebrates and other small animals. The special method adopted for capturing lion tamarins for the Leontopithecus biological bank in Tijuca led to the discovery of six natural shelters. Of these, four belonged to L.r. rosalia and two to L.r.chrysopygus. Worthy of mention is the difference in height of the refuge entrances, located from 1.5 to 15m above the forest floor. Originally, the lion tamarins inhabited primary forests. Today, due to the intense alteration of their habitats, especially that of the nominal race, the remaining populations of these rare marrnosets live in greatly deteriorated or secondary forests. The ongoing destruction of their habitats is reason enough for considering these subspecies as seriously threatened with extinction. However, measures are being taken to preserve L. rosalia, a goal, hopefully, soon to be realized.